The Influence of Using Social Media on Student Learning Achievement in Introductory Economics Subject - Desti Nur Shifa; Supriyadi Supriyadi (Jurnal Ilmiah Profesi Pendidikan, 2023)
The use of social media is almost used by all levels of society. This study aims to reveal the effect of social media (X) on student achievement (Y). This study uses a type of quantitative research with a survey approach. The sample of this research used random sampling technique. The number of research samples was 52 students. Data collection uses valid and reliable instruments. Data analysis using simple regression. the results of the study revealed: (1) Linear Regression Linear Equation Y = 32.940 + 0.466 X (2) the use of social media has a positive effect on student achievement. (3) The significance test obtained by the equation of the F hit regression line is smaller than 0.05, thus, Y or X regression is significant or the intensity of device use affects students' emotional intelligence. (4) The correlation coefficient (rxy) = 0.137 and Fhit (Fchange) = 7.971, with a pvalue less than 0.05. Thus, the correlation coefficient X and Y is meaningful or significant. The coefficient of determination is 0.137, which implies that 13.7% is the variation in the learning achievement variable.